2011
DOI: 10.1063/1.3559136
|View full text |Cite
|
Sign up to set email alerts
|

Burst synchronization transitions in a neuronal network of subnetworks

Abstract: In this paper, the transitions of burst synchronization are explored in a neuronal network consisting of subnetworks. The studied network is composed of electrically coupled bursting Hindmarsh-Rose neurons. Numerical results show that two types of burst synchronization transitions can be induced not only by the variations of intra- and intercoupling strengths but also by changing the probability of random links between different subnetworks and the number of subnetworks. Furthermore, we find that the underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(77 citation statements)
references
References 60 publications
2
75
0
Order By: Relevance
“…Firing patterns in the excitatory synaptic coupled preBötC neurons exhibit in-phase and anti-phase bursting (or spiking) under different initial conditions (Sun et al 2011). When the initial conditions for two-coupled neurons are same, the system will exhibit in-phase bursting.…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firing patterns in the excitatory synaptic coupled preBötC neurons exhibit in-phase and anti-phase bursting (or spiking) under different initial conditions (Sun et al 2011). When the initial conditions for two-coupled neurons are same, the system will exhibit in-phase bursting.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Smith et al further investigated the frequency control and synchronization of these model neurons when coupled by excitatory synapses, simulations of pairs of identical cells revealed that increasing tonic excitation increases the frequency of synchronous bursting (Butera et al 1999b). Bursting and complex synchronous behaviors are important aspects in the study of rhythm dynamics of complex neuronal system (Wang et al 2011;Guo et al 2012;Sun et al 2011;Perc and Marhl 2004a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the wellknown neuron models, networks with different topological connections have been set to investigate the synchronization stability [36,37], pattern selection, and mode transition in collective behaviors [38][39][40][41][42][43][44][45]. Indeed, reliable and biophysical neuron model is critical and important for further investigation on neurodynamics and potential mechanism of some neuronal diseases [46].…”
Section: Complexitymentioning
confidence: 99%
“…Synchronization, as an emerging phenomenon of a population of dynamically interacting units (Arenas et al 2008;Wang and Jiao 2006;Wang and Zhang 2003;Zhang et al 2010), has been extensively studied both in coupled cells (Wang et al 2011;Marek and Stuchl 1975) or complex networks (Gomez-Gardenes et al 2007;Volman et al 2011;Sun et al 2011). It has been demonstrated that the electrical activity of two electrically coupled b-cells can exhibit different forms of synchronous activities, both in vivo (Valdeolmillos et al 1996) and in vitro (Eddlestone et al 1984).…”
Section: Introductionmentioning
confidence: 99%